Proceedings of the ACM/IEEE SC2004 Conference
DOI: 10.1109/sc.2004.56
|View full text |Cite
|
Sign up to set email alerts
|

The Inca Test Harness and Reporting Framework

Abstract: Virtual organizations (VOs), communities that enable coordinated resource sharing among multiple sites, are becoming more prevalent in the high-performance computing community. In order to promote cross-site resource usability, most VOs prepare service agreements that include a minimum set of common resource functionality, starting with a common software stack and evolving into more complicated service and interoperability agreements. VO service agreements are often difficult to verify and maintain, however, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The probe itself is a simple shell script requiring a single core that is submitted through the nanoHUB jo submission process in the same manner as a production application run. In most cases the probe will wait in a batch queuing time prediction, as well as detection of problems in the [3], and TeraGrid's provide information system performance while INCA [5] provides automated testing and monitoring of the grid Yoshimoto [6] evaluated the performance of a variety of resource selection tools against jobs sent to TeraGrid resources and found that the tools do provide improvement over random er, the variety of computing resources utilized by nanoHUB required a more general approach, which we…”
Section: The Grid Probe Systemmentioning
confidence: 99%
“…The probe itself is a simple shell script requiring a single core that is submitted through the nanoHUB jo submission process in the same manner as a production application run. In most cases the probe will wait in a batch queuing time prediction, as well as detection of problems in the [3], and TeraGrid's provide information system performance while INCA [5] provides automated testing and monitoring of the grid Yoshimoto [6] evaluated the performance of a variety of resource selection tools against jobs sent to TeraGrid resources and found that the tools do provide improvement over random er, the variety of computing resources utilized by nanoHUB required a more general approach, which we…”
Section: The Grid Probe Systemmentioning
confidence: 99%
“…Similarly, science portal systems do not easily fit within a traditional ''white-box'' style of unit testing, which assumes knowledge of the source code of all parts of the system, since they depend both on remote clients (users' browsers) and remote Web services that in turn wrap binary executables. The Inca project (SMALLEN et al, 2004) is an example effort in Grid testing and monitoring. User interface-driven testing, such as is needed by science portals, is an open area of systems research, but can be very useful as a way of encapsulating composite tests that simulate real usage scenarios.…”
Section: Unit and System Testing Of Grid Deploymentsmentioning
confidence: 99%
“…Inca [25] is a flexible framework for performing periodic user-level functionality testing and performance measurement of Grid systems. It consists of a reporter repository that contains a collection of reporters (i.e., test programs), reporter managers that are responsible for managing the schedule and execution of reporters on resources, and a depot that is responsible for storing the data produced by reporters.…”
Section: Related Workmentioning
confidence: 99%